The projected gravitational potential of the galaxy cluster MACS~J1206 derived from galaxy kinematics - Stock, Dennis; Meyer, Sven; Sarli-Waizmann, Eleonora; Bartelmann, Matthias (Arxiv, 2015)
We reconstruct the radial profile of the projected gravitational potential of the galaxy cluster MACS-J1206 from 592 spectroscopic measurements of velocities of cluster members. For doing so, we use a method we have developed recently based on the Richardson-Lucy deprojection algorithm and an inversion of the spherically-symmetric Jeans equation. We find that, within the uncertainties, our reconstruction agrees very well with a potential reconstruction from weak and strong gravitational lensing as well as with a potential obtained from X-ray measurements. In addition, our reconstruction is in good agreement with several common analytic profiles of the lensing potential. Varying the anisotropy parameter in the Jeans equation, we find that isotropy parameters which are either small, $β\lesssim0.2$, or decrease with radius yield potential profiles which strongly disagree with that obtained from gravitational lensing. We achieve the best agreement between our potential profile and the profile from gravitational lensing if the anisotropy parameter rises quite steeply to $β≈0. 6$ within $≈0.5\,Mpc$ and stays constant further out.
Gesehen am 15.09.2017